MODERN PRINCIPLES OF FEEDING UP - I.Yu. Mel'nikova ("Paediatrician" Publishers LLC, 2009)
The article presents the main principles of optimal nutrition organization in infants. According to the «National Program of Nutrition of Infants Optimization in Russian Federation» (2009), accepted on ХVI Congress of Pediatrists of Russia, the terms of feeding up are revised. Taking into account the data from studies of leading Russian specialists-nutriciologists, the article considers the expediency and queue of different types of a lure. Key words: infants, nutrition, lure. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):121-125)